2014
DOI: 10.1007/s10237-014-0570-z
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic risk stratification using computational modeling in patients with coronary artery aneurysms following Kawasaki disease

Abstract: Kawasaki disease (KD) is the leading cause of acquired heart disease in children and can result in life-threatening coronary artery aneurysms in up to 25 % of patients. These aneurysms put patients at risk of thrombus formation, myocardial infarction, and sudden death. Clinicians must therefore decide which patients should be treated with anticoagulant medication, and/or surgical or percutaneous intervention. Current recommendations regarding initiation of anticoagulant therapy are based on anatomy alone with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 50 publications
3
53
1
Order By: Relevance
“…The chronic risk of thrombosis is greatest in those with giant aneurysms and is attributable to reduced shear stress and flow disturbances (stagnation) as noted in rheological studies 361,362 and flow simulations. 363,364 Other patient and aneurysm characteristics can also increase thrombosis risk ( Table 9). The degree to which both local and systemic endothelial dysfunction and inflammation contribute to thrombosis risk is not completely known.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…The chronic risk of thrombosis is greatest in those with giant aneurysms and is attributable to reduced shear stress and flow disturbances (stagnation) as noted in rheological studies 361,362 and flow simulations. 363,364 Other patient and aneurysm characteristics can also increase thrombosis risk ( Table 9). The degree to which both local and systemic endothelial dysfunction and inflammation contribute to thrombosis risk is not completely known.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…as in aneurysms), particles that have previously accumulated a high shear history could potentially be advected to the wall even by a lower shear flow that would result in low WSSs on the endothelium. In this case, the computed TFP may provide much more information than simply a WSS-based parameter like ECAP, a measure such as (near wall) residence time, or a single measure of platelet shear history [31,37,40,41]. That is, the present findings motivate further consideration of the TFP, or a similarly combined index, that accounts for the potential of activated platelets being presented to a quiescent (non-thrombogenic) versus a susceptible (thrombogenic) endothelium.…”
Section: Discussionmentioning
confidence: 73%
“…11,14 The present study is the first to evaluate CAA caused by KD using TAG analysis. We found significantly lower TAG values for aneurysmal compared with nonaneurysmal arteries.…”
Section: Discussionmentioning
confidence: 96%
“…Invasive methods such us Doppler flow wire measurements 1012 and patient-specific blood flow simulations in KD patients 13,14 reported abnormal hemodynamics in CAA and showed that hemodynamic parameters may be a promising approach for CAA assessment, in particular for identifying aneurysmal regions at higher risk of thrombosis. 11,14 The present study is the first to evaluate CAA caused by KD using TAG analysis.…”
Section: Discussionmentioning
confidence: 99%